1996
DOI: 10.1177/014107689608901106
|View full text |Cite
|
Sign up to set email alerts
|

Self-Administered Disposable Micro-Enemas before Outpatient Sigmoidoscopy

Abstract: Many colorectal carcinomas can be diagnosed by rigid sigmoidoscopy. One important limiting factor in the usefulness of this investigation is the presence of faeces; another is inability to negotiate the recto-sigmoid bend. 101 patients (47 men) were sent a Microlax enema with instruction to use it before their first attendance in the outpatient department. The grade of preparation [on a scale of 0 (empty rectum) to 3, with grades 0 and 1 providing an adequate view], height achieved with the sigmoidoscope and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Poor bowel preparation occurred in 16.8% of patients. While sigmoidoscopy can be done in poorly prepared patients, it is possible to get an acceptable view in 50% of these patients only, 6 thus making gut preparation preferable. The majority (94%) of our patients tolerated the procedure well, in contrast to other studies.…”
Section: Years)mentioning
confidence: 99%
“…Poor bowel preparation occurred in 16.8% of patients. While sigmoidoscopy can be done in poorly prepared patients, it is possible to get an acceptable view in 50% of these patients only, 6 thus making gut preparation preferable. The majority (94%) of our patients tolerated the procedure well, in contrast to other studies.…”
Section: Years)mentioning
confidence: 99%
“…Although isolated studies have shown that limitation of rigid sigmoidoscopy by the presence of faeces is uncommon [ 7], most recent studies emphasize that views are suboptimal in over 50% of patients who undergo rigid sigmoidoscopy without bowel preparation [ 3–6]. The notion that enemas or suppositories may simulate or conceal signs of disease [ 1, 2] has been refuted by a number of studies [ 3–6], including the present one.…”
Section: Discussionmentioning
confidence: 91%
“…Although isolated studies have shown that limitation of rigid sigmoidoscopy by the presence of faeces is uncommon [ 7], most recent studies emphasize that views are suboptimal in over 50% of patients who undergo rigid sigmoidoscopy without bowel preparation [ 3–6]. The notion that enemas or suppositories may simulate or conceal signs of disease [ 1, 2] has been refuted by a number of studies [ 3–6], including the present one. Evacuation of the rectum, either voluntarily [ 5] or with the aid of enemas or suppositories [ 3–6], has been shown significantly to improve quality of views on rigid sigmoidoscopy and increase distances reached from the anal verge.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations